2014
DOI: 10.12816/0006083
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Care Knowledge and Practices among Mothers Attending Pediatric Outpatient Clinic of a Hospital in Karachi , Pakistan

Abstract: Objectives: To assess newborn care knowledge and practices among mothers. Methodology:A cross-sectional study was conducted at a tertiary care hospital in Karachi, Pakistan. A total of 170 mothers accompanying their infants attending the Paediatric Out Patient Department were interviewed through a structured questionnaire. Areas of inquiry included Antenatal care seeking, delivery care, cord care, eye care, bathing and breastfeeding practices.Results: Ninety-two percent mothers reported at least one antenatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 12 publications
4
35
1
Order By: Relevance
“…Some variation in rates between sites may have been due in part to health system-wide disruptions in service delivery (e.g., floods in Pakistan, 2010; health worker strikes in Kenya, 2012). However, the lower rates of EIBF and EBF observed in the Pakistan site in the current study have also been noted in prior investigations [23,24]. It is interesting to note that the Pakistan site differs from others within the Global Network, in that women face many additional risk factors that have been shown, in previous studies, to interfere with EIBF.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Some variation in rates between sites may have been due in part to health system-wide disruptions in service delivery (e.g., floods in Pakistan, 2010; health worker strikes in Kenya, 2012). However, the lower rates of EIBF and EBF observed in the Pakistan site in the current study have also been noted in prior investigations [23,24]. It is interesting to note that the Pakistan site differs from others within the Global Network, in that women face many additional risk factors that have been shown, in previous studies, to interfere with EIBF.…”
Section: Discussionsupporting
confidence: 84%
“…It is interesting to note that the Pakistan site differs from others within the Global Network, in that women face many additional risk factors that have been shown, in previous studies, to interfere with EIBF. These include: higher rates of women who have no formal education (83%); women with higher parity (47% parity of 2 or more); later initiation of antenatal care in the 3rd trimester (44%); higher percentage of babies who required resuscitation (5%); and the lowest rate of babies placed on the mother’s chest after delivery (7%) [23-26]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding immunization almost all mother vaccinated their child against antigen provided by the government as these two VDCs are hundred percent immunized VDC. Place of birth of the baby was associated with high knowledge on newborn care, and the findings of the study were supported by the study conducted in Pakistan where home delivery was a risk factor for poor cord care(OR=4.07) place of delivery was also associated with bathing (15) . In this study, we found that parity of mother was associated with safe practices for newborn care where the p-value is <0.03 and findings contrast to the study conducted in Chitwan district where they did not recognize parity as one of the factors for neonatal care and odds ratio was less than one (16) .…”
Section: Discussionsupporting
confidence: 71%
“…In our study, we found that the rate of EIBF in the intervention group was 89.1%, which is higher than the values reported for studies in Pakistan and India, but lower than that in Nepal (Khanal, Scott, Lee, Karkee, & Binns, ; Patel et al, ; Zafar, Fatmi, & Shafi, ). There are multiple factors, including maternal education, multiple births, type of delivery, not putting the baby to the breast after birth, and low birthweight, that are associated with a lack of EIBF (Acharya & Khanal, ; Gul, Khalil, Yousafzai, & Shoukat, ; Khadduri et al, ; Sharma & Byrne, ). Our study has also shown that maternal education, low birthweight, and caesarean delivery were associated with late initiation of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%